Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Mutillidae - Gadallah, Neveen S.; Lelej, Arkady S.; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Mutillidae is provided here. The list includes 64 identified species in 21 genera and five subfamilies: Dasylabrinae (2 genera, 16 species), Mutillinae (14 genera, 37 species), Myrmillinae (3 genera, 6 species), Pseudophotopsidinae (1 genus, 4 species), and Ticoplinae (1 genus, 1 species). Distributions, both on the Peninsula and extra-limital, are provided for each species; 31 species (50%) are endemic to the Arabian Peninsula.